2012
DOI: 10.2135/cropsci2012.04.0228
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architecture of Seed Dormancy in U.S. Weedy Rice in Different Genetic Backgrounds

Abstract: Seed dormancy (SD) is a key domestication trait closely related to preharvest sprouting tolerance. Wild and weedy rices ißryza spp.) exhibit higher degrees of seed dormancy compared to the cultivated rice. Red rice {Oryza sativa L.), a major weed in the rice growing areas of the southern United States, was used to elucidate the genetic architecture of SD. Quantitative trait loci (QTL) analysis conducted in two recombinant inbred line (RIL) populations developed from the crosses involving two rice cultivars (Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 59 publications
(99 reference statements)
1
50
0
Order By: Relevance
“…More QTL were detected for wild and crop-mimic traits in this than in the reported research on weedy rice (Bres-Patry et al 2001; Gu et al 2005a; Jing et al 2008; Subudhi et al 2012; Thurber et al 2013). In addition to the difference in the parental combination of mapping population from the previous research, a larger population size, the greenhouse condition, and more trait measurements used in this research must have also contributed to the QTL detection.…”
Section: Discussionmentioning
confidence: 43%
“…More QTL were detected for wild and crop-mimic traits in this than in the reported research on weedy rice (Bres-Patry et al 2001; Gu et al 2005a; Jing et al 2008; Subudhi et al 2012; Thurber et al 2013). In addition to the difference in the parental combination of mapping population from the previous research, a larger population size, the greenhouse condition, and more trait measurements used in this research must have also contributed to the QTL detection.…”
Section: Discussionmentioning
confidence: 43%
“…This Rc -specific pattern suggests that selection may be playing a role in elevating Rc allele frequencies in Malaysian weedy rice. Given the known functional importance of Rc in maintaining rice seed dormancy (Gu et al 2011; Subudhi et al 2012), this disproportionate occurrence of wild-type Rc alleles could potentially reflect selection to maintain seed dormancy alleles introgressed from wild O. rufipogon into Malaysian weed populations.…”
Section: Resultsmentioning
confidence: 99%
“…However, the adaptive value of functional Rc alleles may be more likely to come from the gene’s effects in maintaining seed dormancy. The ability of agricultural weed seeds to remain dormant in the soil over multiple planting seasons plays a key role in their persistence and proliferation (Delouche and Labrada 2007; Vigueira et al 2013b), and the Rc locus has been identified as one of the two major effect QTL for seed dormancy in United States weedy rice (Subudhi et al 2012). While the functional effects of Rc sequence variation on seed dormancy have not been explicitly examined, it is reasonable to expect that wild-type sequences that can successfully regulate proanthocyanidin synthesis would also be functional in establishing seed dormancy.…”
Section: Discussionmentioning
confidence: 99%
“…The QTLs for SD and SH were reported earlier for both RIL populations [21, 22]. Here, we report the results for the agronomic traits that were subjected to QTL analysis using composite interval mapping.…”
Section: Resultsmentioning
confidence: 75%